AI and Democracy: the Role of the European Parliament in shaping the EU “AI Act” - Cinquanta, Raffaella (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
The paper aims at highlighting the political role played by the European Parliament in the drafting of the 2024 EU AI Act: placing it in an ethic and human-centred framework, focusing on regulating the impact of AI on democracy and guaranteeing its consistency with EU founding values. The research follows the “procedure file” process, analysing the reports of the EP special and internal committees. The goal is to define, also in comparison with the Council’s approach, the specific political vision which underpins the EP legislative action: the need to rethink the social contract at the heart of democracies, defining a new model of democratic governance built around technology.